Noise Helps Optimization Escape From Saddle Points in the Synaptic Plasticity - Fang, Ying; Yu, Zhaofei; Chen, Feng (Frontiers in Neuroscience, 2020)
Numerous experimental studies suggest that noise is inherent in the human brain. However, the functional importance of noise remains unknown. Especially, from a computational perspective, such stochasticity is potentially harmful to brain function. In the machine learning, a large number of saddle points are surrounded by high error plateaus and give the illusion of the existence of local minimum. As a result, being trapped in the saddle points can dramatically impair learning, and adding noise will attack such saddle point problem in high-dimensional optimization, especially under the strict saddle condition. Motivated by these arguments, we propose one biologically plausible noise structure and demonstrate that noise can efficiently improve the optimization performance of spiking neural networks based on stochastic gradient descent. The strict saddle condition for synaptic plasticity is deduced, and under such condition, noise can help optimization escape from saddle points on high dimensional domains. The theoretical results explain the stochasticity of synapses and guide us on how to make use of noise. In addition, we provide biological interpretations of proposed noise structure from two points: one based on the free energy principle in neuroscience and another based on observations in vivo experiments. Our simulation results manifest that in the learning and test phase, the accuracy of synaptic sampling with noise is almost 20% higher than that without noise for synthesis dataset, and the gain in accuracy with/without noise is at least 10% for the MNIST and CIFAR-10 dataset. Our study provides a new learning framework for the brain and sheds new light on deep noisy spiking neural networks.